MANAJEMEN PERUBAHAN PADA PERUSAHAAN KELUARGA: STUDI KASUS PT RODA BAHARI - Arie Wibowo Irawan (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2018)
ABSTRACTFamily business is the main driving of Indonesian economy. This sector contribute about 82,44% of total Indonesian GDP. The number of family business is about 99% of total Small Medium Enterprise (SME) in Indonesia. However, only a little family business can survive and scalling up. PT. Roda Bahari that become object of this research is one of the family business. The aim of this research is to analyze change management process and company cycle. This research is important to formulate and prepare for every stage of the transformation process required by PT. Roda Bahari in order to create a professional business entity. The study was conducted in Bogor. The method analysis used is descriptive and the type of data is qualitative. Qualitative data collection was done by interviews and FGD (Focus Group Discussion). The number of responden are 10 person including stakeholder, top management, and staff. To identify the changes that has occured was used Lewins Three Step Model and to identify the changes that will be done was used Kotter Eight Stage Change Process. The result shows that this family business currently in managing phase indicated by company's growth and involvement of the extended family. In order to move to the next phase (transformation phase), PT. Roda Bahari should apply change management. This change management process, require internal agent of change, who has competency, involve in day to day business, and also has strategic access to owner. Based on the identification using Kotter theory, it is known that PT. Roda Bahari should make change in organizational structure, corporate culture, and company policies toward transformation phase.Key Words: Family Business, Change Management, Company Cycle